PENGEMBANGAN APE KOTAK PINTAR UNTUK MENSTIMULASI PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN PADA TAHUN AAJARAN 2022/2023 - Rina Juliana; Abdul Kadir Jaelani; Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to develop a Smart Box app for children aged 5-6 years. Type of development research (R&D) with the ADDIE research method (Analyze, Design, Development, Implementation, and Evaluate). The subjects used in this research were 12 children aged 5-6 years. The data collection method uses observation and the data analysis technique used is descriptive qualitative. The score results from this research and development were that in the first trial the APE Kotak Pintar got a score of 17 with a percentage of 53.2%, then in the second trial it got a score of 23 with a percentage of 71.8%, for the third trial it got a score of 28 with a percentage of 87. .5% and in the fourth or final trial, they got a score of 30 with a percentage of 93.7%. The results of the cognitive development of children aged 5-6 years had increased, which can be seen from the final results of the trial, the average child was in the Very Well Developed category. (BSB). Based on the results above, it can be concluded that the APE Smart Box can stimulate cognitive development in children aged 5-6 years.